2009
DOI: 10.1007/s00270-009-9531-9
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Centerline of Flow Measurement for Sizing of the Zenith AAA Endovascular Graft and Predictive Factor for Risk of Inadequate Sizing

Abstract: The purpose of this study was to evaluate the accuracy of centerline of flow (CLF) measurement for precise sizing of the Zenith AAA endovascular graft (Zenith) and to identify predictive factors of risk of inadequate endograft sizing. We analyzed 42 consecutive patients treated using the Zenith with pre- and postoperative multidetector CT between 2001 and 2007. Endograft sizing was retrospectively performed using CLF on a three-dimensional workstation. The following parameters were investigated: (a) change in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 14 publications
1
24
0
Order By: Relevance
“…The subject population was small. Although our previous retrospective study indicated tortuosity index of the infrarenal abdominal aorta >20 mm as a predictive factor for inadequate endograft design including the overlong main body, 14 median tortuosity index of the infrarenal aorta was 5 mm (range: 1-15 mm) in the present study. We do not make sure that CLF measurement can contribute to selection of device in patients with inadequate anatomy (exclusion criteria), especially severe tortuous neck.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…The subject population was small. Although our previous retrospective study indicated tortuosity index of the infrarenal abdominal aorta >20 mm as a predictive factor for inadequate endograft design including the overlong main body, 14 median tortuosity index of the infrarenal aorta was 5 mm (range: 1-15 mm) in the present study. We do not make sure that CLF measurement can contribute to selection of device in patients with inadequate anatomy (exclusion criteria), especially severe tortuous neck.…”
Section: Discussionmentioning
confidence: 59%
“…Both axial CT and angiography with measurement catheters result in significant differences, particularly shortening. 9,14 There were statistically significant differences in measurements of L1, L2, and L3 between CLF measurement and axial CT measurement in this study. Moreover, there were several discrepancies in device size selected by between CLF measurement and axial CT measurement.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Sobocinski et al demonstrated that the proper utilization of a 3D workstation resulted in less type I endoleaks and secondary interventions when compared to preprocedure imaging evaluation solely by axial 2D CTA (48). CTA 3D reconstruction can also utilize a centerline flow rendering of the aorta and aneurysm, which produces orthogonal images that can be used for pre-procedure imaging evaluation for EVAR, providing an accurate method for aortic measurements (33,51,52). Production of orthogonal images minimizes the inaccurate measurements of a tortuous aorta by allowing for perpendicular measurements.…”
Section: Image Processing Toolsmentioning
confidence: 99%